Pengaruh Anggaran Terhadap Kinerja Manajerial pada PT. Duta Marga Lestarindo - Lukman Nasution; Reza Nurul Ichsan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine and analyze the influence of budget on managerial performance at PT. Ambassador Marga Lestarindo Medan. So the formulation of the problem is "What is the Influential Perspective on Managerial Performance at PT. Ambassador Marga Lestarindo Medan ". Collecting method used is literature research and field research and data analysis that is descriptive method and simple linear regression analysis to test the influence of dependent variable and independent variable. Can be concluded from the test results obtained tcount> ttable (8.143> 2.048) which means that the budget has a significant effect on managerial performance. Regression value obtained is Y = 4.357 + 0.786X, can mean that managerial performance will be worth of 4.357 when the budget value is 0 (no). And the value of X = 0.786 states that the increase in budget will increase managerial performance by 0.786. Value R2 = 0.703, meaning that the effect of the influence of managerial performance of 70.3%.